(untitled) (Takwil: Journal of Quran and Hadith Studies, 2026)
This research examines how digital hermeneutics and Islamic psychology operate in the interpretation of the Qur’an within TikTok-based da’wah content in Indonesia. It addresses four key aspects, namely: the distinctive features of Qur’anic interpretation on TikTok, the influence of platform algorithms in shaping interpretive patterns, the psychological mechanisms through which audiences receive and internalize Qur’anic messages, and the broader epistemological, psychological, and social consequences of this trend. A qualitative design is employed, combining digital content analysis, direct observation, interviews with da’wah content creators, and surveys of TikTok users. The study draws on critical hermeneutics, mediatization of religion theory, and Islamic psychology to explore the dynamic relationship between sacred text, technological systems, and human psychological processes. The findings indicate that interpretations circulating on TikTok tend to be fragmented, context-driven, and closely tied to algorithmic preferences. Qur’anic messages are often framed as motivational or emotionally engaging narratives that resonate with everyday life, placing greater emphasis on the affective dimension (qalb) rather than deeper cognitive reflection (‘aql). In addition, there is a noticeable shift in religious authority, moving away from traditionally recognized scholars toward digital creators whose influence is largely shaped by popularity. The interaction between creators and audiences also fosters a more participatory and dialogical form of interpretation. However, this openness can lead to oversimplification and potential misinterpretation, especially in contexts where digital literacy remains limited. Overall, the study suggests that integrating digital hermeneutics with Islamic psychology creates new opportunities to broaden access to religious knowledge and experience, while at the same time raising concerns about interpretive depth, the reliability of knowledge, and the tendency toward instant meaning-making. Consequently, a more balanced approach is required one that integrates the richness of classical exegesis, psychological insight, and effective digital communication strategies in contemporary da’wah practices.